OPTIMALISASI PERAN KARANG TARUNA MELALUI PENGEMBANGAN WISATA EDUKASI BERBASIS ECOLOGICAL CITIZENSHIP DI DESA SELEMAK - Dharma, Surya; Perangin-angin, Reh Bungana Beru; Sinaga, Osberth; Putra, Mulhady; Jahro, Iis Siti; Junaidi, Junaidi (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
Selemak Village faces a serious environmental issue due to high levels of pollution caused by unmanaged goat farming waste. In response to this problem, a community empowerment program was implemented by providing assistance to the local youth organization (Karang Taruna) in developing educational tourism based on the concept of ecological citizenship. The method used in this program was Participatory Action Research (PAR), which was carried out in three stages. The Preparation Stage involved: (1) program planning, (2) focus group discussions (FGDs), and (3) community service socialization. The Implementation Stage included: (1) livestock pen construction training, (2) educational tourism development assistance, and (3) ongoing mentoring. The Evaluation Stage comprised: (1) a pre-test and (2) a post-test. The results show that this program successfully optimized the role of Karang Taruna in Selemak Village through training in processing goat manure into organic fertilizer. The activities were conducted using a participatory approach through educational sessions, technical guidance, and hands-on field practice. Participants demonstrated high enthusiasm and active engagement throughout the entire program. Evaluation through pre-tests and post-tests, analyzed using a paired-samples t-test, showed a significant improvement, with a p-value of < 0.001. These findings indicate that the program effectively enhanced participants' understanding and skills in waste management based on the principles of ecological citizenship.  Desa Selemak mengalami permasalah dalam tingginya tingkat pencemaran lingkungan akibat limbah ternak kambing yang tidak terkelola dengan baik. Maka berdasarkan permasalahan yang dihadapi dilakukan kegiatan Pendampingan kepada Karang taruna dalam pengembangan wisata edukasi berbasis Ecological citizenship. Metode kegiatan menggunakan Participatory Action Research dengan alur kegiatan yaitu Tahap Persiapan melibatkan: (1) Perencanaan Pelaksanaan, (2) Focus Group Discusion, dan (3) Sosialiasi PKM. Tahap Pelaksanaan terdiri atas: (1) Pelatihan Pembuatan Kandang, (2) Pendampingan Pengembangan Wisata, dan (3) Mentoring. Tahap Evaluasi terdiri atas: (1) Pre-test, (2) Post-test. Hasil kegiatan menunjukkan bahwa Program ini berhasil mengoptimalkan peran Karang Taruna Desa Selemak melalui pelatihan pengolahan limbah kohe kambing menjadi pupuk kandang organik. Kegiatan dilakukan secara partisipatif melalui sosialisasi, pendampingan teknis, dan praktik lapangan. Peserta menunjukkan antusiasme tinggi dan keterlibatan aktif dalam seluruh rangkaian kegiatan. Hasil evaluasi pretest dan posttest yang dianalisis dengan paired sample t-test menunjukkan peningkatan signifikan, dengan nilai signifikansi < 0,001. Temuan ini menunjukkan bahwa program pendampingan efektif dalam meningkatkan pemahaman dan keterampilan peserta dalam pengelolaan limbah berbasis prinsip Ecological citizenship.